Protocol for assessing T cell receptor-mediated human T cell cytotoxicity - Kathryne E. Marks; Ifeoluwakiisi Adejoorin; John Sowerby; Deepak A. Rao (STAR Protocols)
Summary: Measuring the cytotoxicity of human T cells is a valuable but challenging task. We present a protocol for assessing the ability of polyclonal human T cells to kill target cells upon T cell receptor (TCR) triggering. We describe steps for preparing L and T cells for the assay and incubation of target cells with effector cells. We detail procedures for assessing cell death by flow cytometry. This protocol can be applied to small numbers of effector cells isolated from patient samples.For complete details on the use and execution of this protocol, please refer to Wang et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.